Analisis Polimorfisme Nukleotida Tunggal (SNP) Daerah 3’UTR Gen LDLR Penduduk Papua - Asri Saffanah Pratiwi; Achmad Taher (Jurnal Natural, 2019)
Single nucleotide polymorphism (SNP) is a single nucleotide difference in the arrangement of DNA base strands that can show genetic variation. The LDLR gene is a low density lipoprotein (LDL-R) receptor gene that functions to regulate cholesterol levels in the blood. The LDLR gene is composed of 18 exons and contains a 3’untranslated region (3’UTR) which plays an important role in regulating gene expression. This study aims to analyze the SNP in an area of 3'UTR LDLR genes from 6 University of Papua students from Papua. The research was carried out by polymerase chain reaction method to multiply the number of target DNA, then sequenced to find out the sequence of nucleotide bases. The results of this study were from 6 individuals, found 2 SNPs at position *52 and *504 with nucleotide diversity (π) of 0.00149. These polymorphisms forms 3 types of haplotypes, namely GG, GA and AA with a haplotype diversity of 0.600 ± 0.215.